Antiviral activity of 1,2,4-triazole derivatives (microreview) - Simurova, Natalia; Mayboroda, Elena (My University, 2021)
Today, 1,2,4-triazole derivatives are the preferred structural moieties in the development of new drugs with a wide range of pharmacological activity, as evidenced by several reviews.This is due to the fact that the triazole ring can be considered a bioisostere of an amide, ester, or carboxyl groups. Relatively low toxicity, good pharmacokinetic and pharmacodynamic properties of triazole, its resistance to metabolic degradation are another advantages. In recent years, against the background of the emergence of new viral infections and the lack of effective chemotherapeutic agents for their treatment, the number of studies on the antiviral properties of 1,2,4-triazole derivatives has significantly increased. In the presented review, we focused on current publications devoted to the study of the antiviral properties of compounds containing the 1,2,4-triazole ring. Isosteric analogs of known drugs, as well as new molecules, are considered.
Keywords: триазол; вірусні інфекції; противірусні засоби; triazole; viral infections; antiviral drugs; кафедра харчової хімії